Government Framework for Agriculture Service Delivery at the Local Level in Nepal - Jaishi, Mahesh; Sharma, Govinda Prasad; Nepali, Purna Bahadur; Gauchan, Devendra; Shrestha, Ram Krishna; Timsina, Krishna Prasad; Neupane, Huma (Nepal Public Policy Review, 2023)
This paper examines the policy, institutional and legal aspects of agriculture service delivery (ASD) of local government in federal Nepal. The aim of this study is to recommend an appropriate framework for improving ASD unit efficiency in delivering agricultural services to citizens. The paper seeks to answer the question of whether the ASD unit of municipalities facilitates a local government framework while discharging their agriculture services to the citizens. To achieve this, both primary and secondary data were used. Primary data were collected through structured interviews of agriculture service takers using stratified random sampling and were accompanied by participant observations, FGDs and KIIs. Secondary data were obtained from government documents. A convergent parallel mix method research design was adopted, which implied abductive reasoning with pragmatist research philosophy. The study found that despite poor facilities and structures at the local level, the client experienced extended agricultural service delivery. Local governments are undergoing a transition in harmonizing institutional and legal policies, as evidenced by the differences in service delivery and expertise. The study identified three areas of demand from people with local authorities viz; infrastructure for basic services, quality extension from professional experts, and prioritization of the agriculture sector. Based on the findings, an enhanced ASD framework at the local level is recommended to meet the quality service needs of diversified clients. In this regard, enhanced municipal capacity is crucial.